Experimental detection of knotted conformations in denatured proteins - Mallam, Anna L. (National Academy of Sciences, 2010)
Structures that contain a knot formed by the path of the polypeptide backbone represent some of the most complex topologies observed in proteins. How or why these topological knots arise remains unclear. By developing a method to experimentally trap and detect knots in nonnative polypeptide chains, we find that two knotted methyltransferases, YibK and YbeA, can exist in a trefoil-knot conformation even in their chemically unfolded states. The unique denatured-state topology of these molecules explains their ability to efficiently fold to their native knotted structures in vitro and offers insights into the potential role of knots in proteins. Furthermore, the high prevalence of the denatured-state knots identified here suggests that they are either difficult to untie or that threading of any untied molecules is rapid and spontaneous. The occurrence of such knotted topologies in unfolded polypeptide chains raises the possibility that they could play an important, and as yet unexplored, role in folding and misfolding processes in vivo.